The Influence of Financial Ratio on Changes in Profit in Mining Companies Listed on The Indonesia Stock Exchange (Bei) - Sastra Karo-Karo; Hartono (International ABEC, 2021)
The purpose of this study was to determine the effect of financial ratios consisting of quick ratio, return on equity, and debt to assets ratio on profit changes in mining companies listed on the Indonesia Stock Exchange. The population in this study were all companies engaged in the coal mining sector which were listed on the Indonesia Stock Exchange until 2019, while the sampling in this study use purposive sampling method with the criteria of coal mining companies that published their financial reports in 2017 to 2019 and have made profits in the 2017 – 2019 financial year period as many as 22 companies. The data testing technique uses multiple linear regression and partial hypothesis testing with a significance level of alpha = 5%. The results of the research show that the financial ratios consisting of the quick ratio, return on equity, and debt to assets ratio has no effect on changes in profits in coal mining companies. In conclusion, this research supports the research conducted by Justina (2015) and Lestari (2020) because Justina and Lestari’s research results showed that financial ratios have no effect on changes in earnings and are contradictory to research done by Prameswari (2018). Prameswari’s research results conclude that the current ratio, debt to equity ratios affects profit growth.